Insights into the epidemiological analysis of subarachnoid hemorrhage burden and trends in middle-aged and elderly populations: a global perspective from the Global Burden of Disease Study 2021 - Chen, Guiming; Cai, Yuzhou; Ju, Meng; Zheng, Xiye; Bai, Peng (Frontiers in Neurology, 2025)
BackgroundSubarachnoid hemorrhage (SAH) represents a critical neurological emergency with substantial morbidity and mortality, particularly affecting middle-aged and elderly populations. While previous studies have documented SAH epidemiology, the relationship between health workforce distribution and SAH burden remains largely unexplored globally. This study analyzed global epidemiological patterns, temporal trends, and novel associations between health workforce categories and SAH burden among adults aged ≥ 45 years from 1990 to 2021.MethodsWe utilized Global Burden of Disease (GBD) Study 2021 data across 204 countries and territories. We calculated age-standardized incidence rates (ASIR), age-standardized prevalence rates (ASPR), age-standardized mortality rates (ASMR), and age-standardized disability-adjusted life years (DALYs) rates (ASDR). Estimated annual percentage changes (EAPCs) assessed temporal trends. We performed age-period-cohort analysis, decomposition analysis, examined associations with socio-demographic index (SDI), conducted frontier analysis, and explored correlations between 22 health workforce categories and SAH burden.ResultsGlobally, SAH incident cases increased from 321,512 to 487,851 (51.7% increase), while prevalent cases rose from 3,074,793 to 5,654,572 (83.9% increase) between 1990 and 2021. Despite increasing absolute numbers, age-standardized rates declined: ASIR (EAPC: −0.65%), ASPR (EAPC: −0.08%), ASMR (EAPC: −1.39%), and ASDR (EAPC: −1.31%). East Asia showed the highest burden. Middle SDI countries had the highest ASIR and ASMR. Decomposition analysis revealed population growth as the primary driver of case increases (190.28% for incidence), while epidemiological improvements caused substantial reductions (−99.26% for incidence). Our novel health workforce analysis revealed that emergency medical workers demonstrated strengthening protective associations with mortality outcomes over three decades, with correlations improving from r = −0.21 to r = −0.30 (p < 0.001) for deaths. Countries with highest SAH mortality had remarkably low emergency medical worker densities (0.47–11.2 per 10,000 population) compared to low-mortality countries (1.7–26.1 per 10,000 population).ConclusionDespite increasing absolute SAH burden, age-standardized rates declined globally, indicating epidemiological improvements. Our novel finding of strong inverse relationships between emergency medical workforce density and SAH mortality provides the first global evidence for targeted healthcare capacity building. These findings offer new insights for optimizing healthcare resource allocation and reducing global SAH burden, particularly in regions with inadequate emergency medical infrastructure.